2009
DOI: 10.1517/17425240903419608
|View full text |Cite
|
Sign up to set email alerts
|

Viral-based gene delivery and regulated gene expression for targeted cancer therapy

Abstract: A summary of existing challenges and future directions is also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…In addition to bacterial treatment, biological therapy with viruses is also being studied by modern research. ( 51,52 ) To discriminate between cancer cells and non‐cancerous cells, genetically engineered oncolytic viruses have been constructed to target tumors by exploiting each cancer’s unique biology. The efficacy can be enhanced by carrying therapeutic genes to induce cellular apoptosis/suicide and/or facilitate tumor/virus imaging.…”
Section: Bacterial Therapy For Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to bacterial treatment, biological therapy with viruses is also being studied by modern research. ( 51,52 ) To discriminate between cancer cells and non‐cancerous cells, genetically engineered oncolytic viruses have been constructed to target tumors by exploiting each cancer’s unique biology. The efficacy can be enhanced by carrying therapeutic genes to induce cellular apoptosis/suicide and/or facilitate tumor/virus imaging.…”
Section: Bacterial Therapy For Cancermentioning
confidence: 99%
“…Some viruses are armed with genes to affect the tumor microenvironment, such as genes encoding for angiostatic factors, inflammatory cytokines, or proteases that modulate the extracellular matrix to suppress tumor vascularization, or to enhance antitumor immune responses and viral spread throughout the solid tumor. ( 51,52 )…”
Section: Bacterial Therapy For Cancermentioning
confidence: 99%
“…Although inducible promoters offer the potential to selectively control therapeutic gene expression in the tumor with little normal tissue toxicity; however, when activated, these promoters often result in lower activity, and transgene expres-sion is limited to the period of stimulation and returns to basal levels following withdrawal of the induction trigger. (26,27) In our experiments, continuous growth inhibition of xenografts with active AND gate genetic circuit demonstrated that after activation, the AND gate vectors could make persistent antitumor effects in vivo and might overcome the temporary expression from inducible promoter.…”
Section: Discussionmentioning
confidence: 80%
“…In recent years, numerous classes of tumour-targeting agents have been developed including small molecules [40], antibodies [41][42][43], nanoparticles [44,45], viral [46][47][48] and non-viral gene vectors [49][50][51], and cell-based vectors [4- 19,[27][28][29][30][31][32]. Traditionally, the development of cellbased therapies has focused on the use of stem-cells including tissue-specific stem cells, pluripotent stem cells or mesenchymal stem cells [5,6,[8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%